Analysis of Promotion, Price Perception, and Product Quality on Yamaha Motorcycle Purchase Decisions in Bintaro, South Tangerang - Azwar, Rully Choiril; Nurmahdi, Adi (Dinasti International Journal of Digital Business Management, 2025)
The increasing public demand for motorcycles has made the level of competition in the automotive industry, especially motorcycles, increasingly tight. This can be seen from the many motorcycle brands that have emerged to meet the needs of consumers. This study aims to determine "Analysis of Promotion, Price Perception, and Product Quality on Yamaha Motorcycle Purchasing Decisions in Bintaro, South Tangerang". From this study, the independent variables consist of Promotion, Price Perception, and Product Quality, and the dependent variable is Purchase Decisions. The population in this study were consumers who had purchased Yamaha Motorcycles in Bintaro, South Tangerang. The analysis techniques used in this study include the outer model test (Convergent Validity, Discriminant Validity, Composite Reliability, Cronbach's Alpha), the inner model test (R-Square, Goodness of Fit Model) Data were collected by distributing questionnaires to consumers and processed using the Smart PLS 4.0 program. The results of this study are Promotion Accepted has a positive and significant effect on purchasing decisions, Price Perception Accepted has a positive and significant effect on purchasing decisions, and Product Quality Accepted has a positive and significant effect on purchasing decisions.